Effect of Urea-Molasses and Lactic Culture on Silage Fermentation of Cenchrus ciliaris - Pancholy, Rakesh; Mali, P C; Mathur, Dinesh (Annals of Arid Zone, 2016)
To study the effect of additives, urea, molasses and lactobacillus cultures, on silage fermentation of Cmchrus ciliaris in arid regions, S treatments with different proportions of urea (1 and 2% OM) and molasses (8%) were studied in laboratory silos. Molasses addition showed a significant effect (P